2D-3D pose estimation - Rosenhahn, B.; Perwass, C.; Granert, O.; Sommer, G. (2006)
This research project deals with the 2D-3D pose estimation problem. Pose estimation itself means to estimate the relative position and orientation (rotation and translation) of a (known) 3D object with respect to a reference camera system.